Remarkably stable amphiphilic random copolymer assemblies: A structure–property relationship study. Issue 22 (11th September 2013) - Dan, Krishna; Rajdev, Priya; Deb, Jolly; Jana, Siddhartha S.; Ghosh, Suhrit
ABSTRACT Synthesis of a library of amphiphilic random copolymers from a single reactive pre‐polymer and their self‐assembly is reported. Post‐polymerization modifications of the parent polymer containing pendant N‐hydroxy succinimide (NHS) ester groups with various oligooxyethylene (OE) amines produce amphiphilic random copolymers with same degree of polymerization and equal extent of randomness. 1H‐NMR and FT‐IR data indicate quantitative substitution in all cases. The critical aggregation concentration (CAC) for all the polymers is estimated to be in the range of 10−5 M. Stability of these nano‐aggregates is studied by photoluminescence using time dependent F—rster Resonance Energy Transfer (FRET) between co‐encapsulated lipophilic dyes namely DiO and DiI in the hydrophobic pocket of the aggregates. These studies suggest remarkably high stability for all systems. However those with shorter hydrophilic pendant chains are found to be even more robust. Morphology is examined by high resolution transmission electron microscopy (HRTEM) which reveals multi‐micellar clusters and vesicles for polymers containing short and longer OE segments, respectively. Encapsulation efficacy is tested with both hydrophobic and hydrophilic guest molecules. All of them can encapsulate hydrophobic guest pyrene while a hydrophilic dye Calcein can be sequestered only in vesicle forming polymers. Lower critical solution temperature (LCST) is exhibited by only one polymer that contains the shortest OE chains. All polymers exhibit excellent cell viability as determined by MTT assay. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4932–4943